O nekotorykh printsipakh obucheniya plavaniyu - Pogrebnoy, A. I.; Maryanicheva, E. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
On some principles and a newly developed method for the training of beginners in swimming, on the base of biomechanical and psycho-paedagogical preconditions. This method divides the whole process into two phases separated fro each other: one which develops the ability to stay on the surface on the water and the othe which develops the ability to propell through the water by different means.